MENGGALI POTRET DR. MARIE THOMAS: DOKTER WANITA PERTAMA INDONESIA - Rahmalia, Arina; Resdiyanti, Lidiya; Afiah, Nur Sobah; Arifin, Faizal (Jazirah: Jurnal Peradaban dan Kebudayaan, 2022)
This research examines the career and contributions of dr. Marie Thomas, the first female doctor in Indonesia. Despite living in a society dominated by colonial and patriarchal culture, dr. Marie Thomas overcame various challenges and became inspirational. The research adopts a historical method of heuristics, criticism, interpretation, and historiography, analyzing primary and secondary sources, including newspapers and documents from the Dutch colonial era. The findings reveal that dr. Marie Thomas was the only female student among male students at the School of Medicine in the Dutch East Indies (School tot Opleiding van Indische Artsen/STOVIA) in 1922. She faced gender stereotypes and limited access to higher education. However, with determination and perseverance, dr. Marie Thomas obtained the title of Indische Arts (Indies Doctor), specializing in obstetrics and gynecology. Her contributions are evident in promoting the role of women in healthcare, particularly in maternal and child health in Indonesia. dr. Marie Thomas serves as an inspiration for future generations of female doctors. This research provides insights into her struggle to transform social paradigms in the medical field in the Dutch East Indies.